The Escherichia coli MutL protein stimulates binding of Vsr and MutS to heteroduplex DNA. - Drotschmann, K (1998)
Vsr DNA mismatch endonuclease is the key enzyme of very short patch (VSP) DNA mismatch repair and nicks the T-containing strand at the site of a T-G mismatch in a sequence-dependent manner. MutS is part of the mutHLS repair system and binds to diverse mismatches in DNA. The function of the mutL gene product is currently unclear but mutations in the gene abolish mutHLS -dependent repair. The absence of MutL severely reduces VSP repair but does not abolish it. Purified MutL appears to act catalytically to bind Vsr to its substrate; one-hundredth of an equivalent of MutL is sufficient to bring about a significant effect. MutL enhances binding of MutS to its substrate 6-fold but does so in a stoichiometric manner. Mutational studies indicate that the MutL interaction region lies within the N-terminal 330 amino acids and that the MutL multimerization region is at the C-terminal end. MutL mutant monomeric forms can stimulate MutS binding.